2020
DOI: 10.1136/bmjopen-2019-034778
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral anticoagulants among patients with atrial fibrillation: a systematic review and meta-analysis of observational studies

Abstract: IntroductionMedications cannot exert their effect if not taken as prescribed by patients. Our objective was to summarise the observational evidence on adherence to oral anticoagulants (OACs) among patients with atrial fibrillation (AF).MethodsIn March 2019, we systematically searched PubMed/Medline, Embase, CINAHL and PsycINFO (from inception) for observational studies measuring adherence, its determinants and impacts in patients with AF. Mean adherence measures and corresponding proportions of adherent patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 81 publications
4
76
4
7
Order By: Relevance
“…The prolongation of PT observed in the present study in patients using Rivaroxaban, in relation to those found for healthy non-medicated individuals is in line with previous studies reported in the literature, such as that by Douxfils et al 9 According to these studies, PT can be used as a screening test to assess bleeding risk, although more specific tests using calibrators should be applied to confirm the plasma concentration of Rivaroxaban. In this regard, ISTH basically defines 2 types of tests for the evaluation of direct oral anticoagulants: simple semiquantitative tests available in most laboratories, and quantitative tests capable of accurately reporting levels of the drug.…”
Section: Table 1 -Prothrombin Time In Patients With Atrial Fibrillatisupporting
confidence: 92%
See 1 more Smart Citation
“…The prolongation of PT observed in the present study in patients using Rivaroxaban, in relation to those found for healthy non-medicated individuals is in line with previous studies reported in the literature, such as that by Douxfils et al 9 According to these studies, PT can be used as a screening test to assess bleeding risk, although more specific tests using calibrators should be applied to confirm the plasma concentration of Rivaroxaban. In this regard, ISTH basically defines 2 types of tests for the evaluation of direct oral anticoagulants: simple semiquantitative tests available in most laboratories, and quantitative tests capable of accurately reporting levels of the drug.…”
Section: Table 1 -Prothrombin Time In Patients With Atrial Fibrillatisupporting
confidence: 92%
“…6 DOACs have been widely used for primary or secondary prevention of stroke in patients with AF, while AF ablation under uninterrupted warfarin or rivaroxaban has shown a safety profile. 7,8,9 However, there is no evidence of benefit of DOACs in patients with mechanical prosthetic valves or moderate/severe mitral stenosis. 6 Direct thrombin inhibitors and factor Xa inhibitors do not usually require laboratory monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…This should encourage us to look for better strategies to improve secondary stroke prevention, such as ensuring patients' adherence to treatment. The NOACISP-LONGTERM registry showed 78.4% of the patients to be fully adherent with a median follow-up of 12 months, and a recent systematic review showed that up to 30% of the patients with AF are non-adherent to any OAC (22,41). Likewise, a Spanish study suggested that only 41.4% of the patients are treated following the current Spanish recommendations in clinical practice (42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physicians worry about the use of OAC drugs, which cause serious bleeding events and prevent thromboembolism. Nonadherence and poor control of PT-INR are known to be independent risk factors for major adverse events, including major bleeding during OAC therapy [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%